Matching N3LO QCD calculations to parton showers - Stefan Prestel (SpringerOpen, 2021)
Abstract The search for new interactions and particles in high-energy collider physics relies on precise background predictions. This has led to many advances in combining precise fixed-order cross-section calculations with detailed event generator simulations. In recent years, fixed-order qcd calculations of inclusive cross sections at n3lo precision have emerged, followed by an impressive progress at producing differential results. Once differential results become publicly available, it would be prudent to embed these into event generators to allow the community to leverage these advances. This note offers some concrete thoughts on me+ps matching at third order in qcd. As a method for testing these thoughts, a toy calculation of e + e − → u u ¯ $$ \overline{u} $$ at O $$ \mathcal{O} $$ ( α s 3 $$ α_s^3 $$ ) is constructed, and combined with an event generator through unitary matching. The toy implementation may serve also as blueprint for high-precision qcd predictions at future lepton colliders. As a byproduct of the n3lo matching formula, a new nnlo+ps formula for processes with “additional” jets is obtained.